1988
DOI: 10.1016/0014-5793(88)80946-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of polypeptide‐chain initiation in rat skeletal muscle Starvation does not alter the activity or phosphorylation state of initiation factor eIF‐2

Abstract: In rats, 48-h starvation causes a decrease in the rate of protein synthesis in skeletal (e.g. gastrocnemius)muscle, due largely to impairment of peptide-chain initiation. In other cell types inhibition of initiation is associated with decreased activity and recycling of initiation factor eIF-2, and increased phosphorylation of its a-subunit. However, 48-h starvation has no effect on the activity or recycling of eIF-2 measured in extracts of gastrocnemius muscle, or on the level of a-subunit phosphorylation.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 30 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…In these experiments insulin did not affect the level of eIF2a phosphorylation as assessed by isoelectric focusing ( = 15% with or without insulin; data not shown). This observation is consistent with other work in muscle [11,13,32,33] and in Swiss 3T3 cells [14] showing that insulin or diabetes do not affect the state of phosphorylation of eIF2a and points to an alternative mechanism regulating the activity of eIF2B.…”
Section: Insulin Activates Eif2b and Inactivates Gsk-3 In Choirsupporting
confidence: 93%
“…In these experiments insulin did not affect the level of eIF2a phosphorylation as assessed by isoelectric focusing ( = 15% with or without insulin; data not shown). This observation is consistent with other work in muscle [11,13,32,33] and in Swiss 3T3 cells [14] showing that insulin or diabetes do not affect the state of phosphorylation of eIF2a and points to an alternative mechanism regulating the activity of eIF2B.…”
Section: Insulin Activates Eif2b and Inactivates Gsk-3 In Choirsupporting
confidence: 93%
“…Previous studies have shown that neither the activity of eIF2B nor the phosphorylation of eIF2␣ in mature rats changes with feeding (4,55). However, we hypothesized that the initiation factors involved in the formation of the 43S preinitation complex might be activated by feeding in immature animals, because the stimulation of muscle protein synthesis by feeding is markedly elevated in the neonate (5,7,9).…”
Section: Discussionmentioning
confidence: 88%
“…These phenomena occur without a detectable change in eIF2B activity (37). Moreover, 48-h starvation is without effect on the activity of eIF2B although protein synthesis diminishes (1). Thus, although protein synthesis is regulated by eIF2B under a variety of circumstances (8), particular nutritional states and glucocorticoid treatment share a mode of regulation mediated by eIF4F and independent of eIF2B.…”
Section: Discussionmentioning
confidence: 98%